URGENSI NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI MADRASAH IBTIDAIYAH (MI) - Munawir, Munawir; Mukaromah, Lu’lu’ul; Firmansyah, Muhammad Rizky (FIKRAH, 2023)
SKI learning in madrasas involves various social contexts and goes beyond just the transfer of historical knowledge. Religious moderation is an important outcome of religious education in Indonesia, and primary and secondary education are prerequisites for continuing to higher education. In this context, educational institutions have an important role in instilling and implementing the values of religious moderation. This study aims to describe the urgency of the value of religious moderation in learning Islamic Cultural History (SKI) at Madrasah Ibtidaiyah (MI). The method used in this study is a literature review by accessing various relevant sources through Google Scholar with a minimum of 5 years published reference articles. The results of the study show that religious moderation is a balanced religious attitude between exclusive religious practices and respect for other people's religious practices. Religious moderation is the key to creating tolerance and harmony in society. SKI learning at MI can be a means to develop religious moderation values in students. By incorporating religious moderation in SKI learning, it is hoped that students can treat each other with respect, accept differences, and live in peace and harmony.